Growth and milk production of dairy heifers born to two-year-old or mixed-age dams - Handcock RC; Lopez-Villalobos N; Back PJ; Hickson RE; McNaughton LR (New Zealand Society of Animal Production, 2019)
Keeping replacement heifers that were the progeny of primiparous cows mated by artificial insemination, enhances rates of genetic gain. Heifers that were the progeny of primiparous cows were lighter at birth and grew at a slower rate to first calving compared with heifers born to multiparous dams. Heifers that were heavier before first calving produced more milk than did lighter heifers. This study aimed to determine if there were liveweight (LWT) or milk-production disadvantages for heifers born from primiparous compared with multiparous dams. Data comprised of LWT records from 189,936 New Zealand dairy heifers. Dams were allocated to four groups according to their age: two (2yo; n=13,717), three (3yo; n=39,258), four to eight (4-8yo; n=120,859) and nine years old or greater (≥9yo; n=16,102). Heifers born to 2yo dams were lighter (P<0.01) from three to 21 months of age than heifers born to 3yo and 4-8yo dams. The progeny of 2yo and 3yo dams produced similar milksolids yields during their first lactation (304.9±1.6 and 304.1±1.5 kg, respectively), but more (P<0.01) than that of 4-8yo dams (302.4±1.5) and ≥9yo dams (P<0.001; 297.8±1.6 kg). Heifers born to 2yo dams were lighter but produced more milk than heifers from older dams.
Keywords: dam; growth; milk; heifer